One Pesantren One Product: Can It Improve Economic Growth in East Java? - Renny Oktafia; Taufiq, M.; Utami, Anisa Fitria (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to determine the implementation of the One Pesantren One Product (OPOP) program in improving the economy of Pesantren in East Java. This research was conducted using qualitative methods, by conducting interviews and documentation at 3 pesantren in East Java. The existence of pesantren in East Java which are increasingly popular, the East Java Provincial Government has launched a new breakthrough for the community program. Governor of East Java Khofifah Indar Parawansa launched One pesantren One Product (OPOP) based on three pillars and five aspects. The increasing number of pesantren implementing the OPOP program will have a direct impact on the economy of pesantren in East Java, for example, namely the Bahrul Maghfiroh, Al Fattah Turen, and Al Yasini pesantren where they have succeeded in growing the independence of pesantren which has a positive impact on the development of their pesantren. Therefore, OPOP is a program that can improve the economy in East Java.